Reproductive and Child Health Related Contents at undergraduate medical level in the Community Medicine - Teachers view - Jahan, Sharmin; Talukder, Md Humayun Kabir (Journal of Dhaka National Medical College & Hospital, 2012)
Objectives: The objectives of this study were to assess the views of teachers regarding the reproductive and child health related contents at the medical undergraduate level in Bangladesh. Methodology: A descriptive type of cross-sectional study was carried out from January 2009 to June 2009 among 30 teachers of government and non government medical colleges in Bangladesh. Data were collected by pre tested self administered semi-structured questionnaire. Results: Results of the study shows that a total of 58% of the teachers feel that topics such as maternal health, infant and child care, family planning and adolescent health might be useful in future life. They have shown more interest towards problem solving class with scenario exercises, group discussions and brain storming sessions. They also feel that clinical oriented topics should be included more. It was also revealed that more than 65% of the teachers feel that RCH related contents are the most important or one of the most important topics in the Community Medicine. Conclusion and recommendation: Some of the non-traditional teaching methods like problem solving class with scenario exercises, group discussions and brain storming sessions may be practiced to improve the teaching and assessment in reproductive and child health related contents at the undergraduate medical level in Bangladesh. DOI: http://dx.doi.org/10.3329/jdnmch.v18i1.12236 J. Dhaka National Med. Coll. Hos. 2012; 18 (01): 29-33